THE COWRIES-SHELLS AND PIGS IN THE HIGHLAND OF PAPUA: THE LAPITA INFLUENCE? (Keberadaan Cangkang Kerang Cowrie dan Babi di Pegunungan Tinggi Papua: Pengaruh Lapita?) - Marlin Tolla (BALAI ARKEOLOGI PAPUA, 2014)
Cowrie shells and pork was instrumental in the life of tribes in Papua. Shellfish and pork cowries used as a medium of exchange, dowry, and death rituals. This paper aims to describe the relationship with the coastal areas of the mountainous region of Papua, as well as the influence of Lapita in the mountains. Data collected by literature study and qualitative descriptive analysis. Shellfish and pork cowries were introduced by Austronesian speakers to the indigenous people in the mountains of Papua. ABSTRAKKerang cowrie dan babi sangat berperan dalam kehidupan suku-suku di pegunungan Papua. Kerang cowrie dan babi digunakan sebagai alat tukar, mas kawin, dan ritual kematian. Tulisan ini bertujuan untuk mendeskripsikan keterkaitan wilayah pesisir Papua dengan wilayah pegunungan, serta pengaruh Lapita di pegunungan. Pengumpulan data dilakukan dengan studi pustaka dan analisis deskriptif kualitatif. Kerang cowries dan babi diperkenalkan oleh penutur Austronesia kepada penduduk asli di pegunungan Papua.